Management of hypertension in obstructive sleep apnea - Yi-Hui Ou; Adeline Tan; Chi-Hang Lee (Elsevier, 2023)
Obstructive sleep apnea (OSA) plays an important role in the development of hypertension. Thus, this review summarizes pharmacological and non-pharmacological approaches to blood pressure (BP) control in patients with OSA. Current treatments for OSA, such as continuous positive airway pressure, are effective at lowering BP. However, they only provide a modest BP reduction, and pharmacological treatment remains important for achieving optimal BP control. Furthermore, current guidelines for the treatment of hypertension do not make specific recommendations on pharmacological treatment protocols for controlling BP in patients with OSA. Moreover, the BP-lowering effects of various classes of antihypertensives may be different in hypertensive patients with OSA than in those without OSA due to the underlying mechanisms that promote hypertension in OSA. The acute and chronic increase in sympathetic nerve activity in patients with OSA explain the effectiveness of beta blockers in controlling BP in these patients. As activation of the renin-angiotensin-aldosterone system may also promote hypertension in OSA, angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers have generally been found effective for lowering BP in hypertensive patients with OSA. The aldosterone antagonist spironolactone also produces a good antihypertensive response in patients with OSA and resistant hypertension. However, there are limited data available that compare the effects of various classes of antihypertensive medication on BP control in those with OSA, and most data have been obtained from small-scale studies. This demonstrates the need for large-scale randomized controlled trials to evaluate a range of BP-lowering regimens in patients with OSA and hypertension.